(3GdHjQRI aj GdHQPQIs
(3ChdgG (B:s
(3PcQ GdKbGJ ef GdQhGI Cgd GdeYQaI Cf GdEScfOQ GdQhei bGd(B: (3ddMceGA GdeNJUjf HNOeJg jhekG s
(3BNQgG (B:s
(3Je GdcJGH HMeO Gddg hYhfg hMSf Jhajbg hGdMeO ddg hMOg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde JSdjekG cKjQkG s
(3LGA HUaMI GdYfhGf (B: (3Ufag GdMceGA GdeJbOehf ddedc GdEScfOQ GdQheis
(3hgh YHGQI Yf (B115 (3HGH hQZe Pdc agPg GdfSNI JfJgi YfO GdHGH (B63s
(3fSNI NRGFfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B22 s
Keywords: (3GdcjejGA h GdWHjYjGJs